2018
DOI: 10.1161/str.49.suppl_1.wmp96
|View full text |Cite
|
Sign up to set email alerts
|

Abstract WMP96: Racial Variation in Comfort Measures Only Status in Patients With Intracerebral Hemorrhage

Abstract: Introduction: Prior studies of critically ill patients found that non-whites are less likely to pursue comfort measures only status (CMOs). We sought to identify determinants of CMOs in a large multi-ethnic cohort study of intracerebral hemorrhage (ICH). Methods: We analyzed cases enrolled from 2010 to 2015 in the Ethnic/Racial Variations of ICH (ERICH) study, a multi-center study in the USA. Clinical, demographic and radiologic data on non-traumatic IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Interestingly, CMO status in the first 24 h of ED arrival was not associated with any acute processes of care. Past findings have shown that white patients with stroke are more likely to pursue CMO and withdraw from life-sustaining interventions compared to minorities [ 19 21 ] and that CMO status may lead to slower care. Contrary to the past findings, we did not find patients made CMO within 24 h of ED arrival to have received slower care.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CMO status in the first 24 h of ED arrival was not associated with any acute processes of care. Past findings have shown that white patients with stroke are more likely to pursue CMO and withdraw from life-sustaining interventions compared to minorities [ 19 21 ] and that CMO status may lead to slower care. Contrary to the past findings, we did not find patients made CMO within 24 h of ED arrival to have received slower care.…”
Section: Discussionmentioning
confidence: 99%